ANALISIS PENGARUH CUSTOMER EXPERIENCE, INTENSITAS PERIKLANAN TERHADAP MINAT BELI GRAMEDIA.COM DENGAN BRAND AWARENESS SEBAGAI VARIABEL INTERVENING (STUDI PADA PELANGGAN GRAMEDIA SEMARANG) - Masyhuri, Mardhi (Proceeding SENDI_U, 2016)
Gramedia bookstore is a company engaged in the retail industry by providing a network of bookstoresacross Indonesia.. Gramedia bookstore launches virtual store from his bookstore is Gramedia.com aimsto expand the market share of the company. However Gramedia.com virtual store is having problems, isthe low purchase intention on Gramedia.com. Seeing these problems, this study aims to analyze the effectof Customer Experience and Advertising Intensity against buying interest using Brand awareness as amediator variable (intervening) study on customer Gramedia bookstore Semarang. This study used nonprobability sampling used for sampling. Data were collected from 117 respondents were selected usingcriteria of judgment that should have never made a purchase products Gramedia bookstore at anybranch. Test method is a Maximum Likelihood analysis with AMOS program version 22.0. The resultshow that the customer experience and the advertising intensity of the positive effect buying interest,either through brand awareness as intervening nor affect directly. Then, brand awareness positive effecton consumer buying interest Semarang Gramedia bookstore to buy a book on the virtual store productsGramedia.com.Keywords: e-commerce, retail, customer experience, Advertising Intensity, brand awareness andpurchase intention.